In Utero Exposure to Metformin Reduces the Fertility of Male Offspring in Adulthood - Faure, Mélanie C.; Khoueiry, Rita; Quanico, Jusal; Acloque, Hervé; Guerquin, Marie-Justine; Bertoldo, Michael J.; Chevaleyre, Claire; Ramé, Christelle; Fournier, Isabelle; Salzet, Michel; Dupont, Joëlle; Froment, Pascal (Frontiers in Endocrinology, 2021)
Metformin is a drug used for the treatment of type 2 diabetes and disorders associated with insulin resistance. Metformin is also used in the treatment of pregnancy disorders such as gestational diabetes. However, the consequences of foetal exposure to metformin on the fertility of exposed offspring remain poorly documented. In this study, we investigated the effect of in utero metformin exposure on the fertility of female and male offspring. We observed that metformin is detectable in the blood of the mother and in amniotic fluid and blood of the umbilical cord. Metformin was not measurable in any tissues of the embryo, including the gonads. The effect of metformin exposure on offspring was sex specific. The adult females that had been exposed to metformin in utero presented no clear reduction in fertility. However, the adult males that had been exposed to metformin during foetal life exhibited a 30% reduction in litter size compared with controls. The lower fertility was not due to a change in sperm production or the motility of sperm. Rather, the phenotype was due to lower sperm head quality – significantly increased spermatozoa head abnormality with greater DNA damage – and hypermethylation of the genomic DNA in the spermatozoa associated with lower expression of the ten-eleven translocation methylcytosine dioxygenase 1 (TET1) protein. In conclusion, while foetal metformin exposure did not dramatically alter gonad development, these results suggest that metabolic modification by metformin during the foetal period could change the expression of epigenetic regulators such as Tet1 and perturb the genomic DNA in germ cells, changes that might contribute to a reduced fertility.